Multiple flare occurrences and the geomagnetic storm characteristics during solar cycle 23 - Alex, S.; Mukherjee, S.; Pathan, B.M. (My University, 2006)
High solar activity occurred during solar cycle 23, having its solar maximum peak in the years 2000 and 2001. The dual peak occurrence of the solar activity as seen in 2003, during the descending phase of the solar cycle suggests the geoeffective nature of the solar activity following the solar maximum. The most remarkable series of activities were seen during these times. Major flares are invariably followed by an abrupt increase in the solar radiation emissions from the sun. Active regions in the sun gave rise to a sequence of X- & M- class flares, a number of coronal mass ejections and several major solar energetic particle events of varying amplitudes and characteristics. Following these energetic emissions, the geomagnetic field variations recorded on the ground experienced several storm phenomena in 2005 unlike the 2003 geomagnetic storm events. Storm manifestation process as seen in the equatorial and low-latitude digital magnetic records from Indian longitude are explained in association with the prolonged fluctuations in the interplanetary magnetic field during the descending phase of the solar cycle in contrast to intense storm feature of the events in 2003.
Keywords: Flares; Geomagnetic storms; Ring current; Interplanetary magnetic field; solar wind parameters; Solar cycle